Supression of ventricular extrasystoles by perhexiline. - Pickering, T G (1978)
The antiarrhythmic effects of perhexiline were investigated in 13 of 20 patients with frequent and long standing ventricular extrasystoles in a double blind crossover trial using 24-hour electrocardiograph tape recordings, routine electrocardiograms, and treadmill exercise testing. With a dose of 300 to 400 mg per day, there was a significant decrease (mean 41%) in the number of ventricular extrasystoles per 24 hours. There were large differences in the individual responses to perhexiline, which were significantly related to the diurnal variations of ventricular extrasystoles: those patients whose ventricular extrasystoles disappeared spontaneously during sleep were less likely to respond to perhexiline than those whose ventricular extrasystoles persisted throughout the night. Suppression of ventricular extrasystoles was also apparent from the routine electrocardiogram and the exercise tests. Side effects (dizziness and unsteadiness) were troublesome in 5 of 20 patients. It is concluded that in selected patients perhexiline is an effective antiarrhythmic drug, and is likely to be most useful in patients with coexisting angina and ventricular extrasystoles. Because of its potential toxicity, it should not be used as a drug of first choice.